Gender issues: the effects of differences in interaction styles between genders and roles on workplace communication / Sharifah Nadhira Syed Iskandar ... [et al.] - Syed Iskandar, Sharifah Nadhira; A. Rahim, Aisyah Munirah; Mohd Yussoff, Aina Nor Syakila; Abu Bakar, Fatin Hanini (Universiti Teknologi MARA Shah Alam, 2018)
Issues related to gender in the workplace are quite a common and debatable issue in Malaysia considering that male employees dominate the working world in general. Gender issues at the workplace has become a problem in the workforce which in return brings negative impacts on the organisations involved as well as the victims themselves without regarding the gender. Given this situation, this study aims to explore the differences in the interaction styles between gender and gender roles in which we would look into how they affect the workplace communication. In addition, workplace has been a war field for female against gender issues. The questionnaires were distributed to the respondents with a working experience regardless of their employment status. A total of 33 questionnaires were completed by the respondents. This quantitative study used descriptive analysis approach in analysing the frequency which was presented in percentage. According to the results obtained it was revealed that most of our respondents agreed with our statements which aligned with our previous researches. Future researches should be conducted in order for these aspects in the issues to be included and discussed holistically.